Meniscal Cysts: Treatment Options and Algorithm - Cowden, Courtney H., III; Barber, F. Alan (The Journal of Knee Surgery, 2014)
Meniscal cysts are commonly seen in the knee. Symptomatic meniscal cysts tend to be located on the lateral side but magnetic resonance imaging studies indicate that medial cysts are more common. Meniscal cysts are commonly associated with horizontal meniscal tears. The arthroscopic management of symptomatic cysts should include debriding the horizontal meniscal tear (if nonrepairable) to fully decompress the cyst and the creation of a 5-mm channel from the joint into the cyst. If a vertical peripheral meniscal tear exists or is created, meniscal repair for appropriately selected cases should be performed.
Keywords: knee; meniscal cysts; arthroscopy